An analysis of the process of ascertainment and application of customary law in the formal institutions of adjudication: Nigeria and South Africa - Badejogbin, Rebecca Emiene (Department of Private Law, 2018)
Judges of formal courts in Nigeria and South Africa do not easily have access to the contents of customary law they are required to apply in the course of adjudication and this has been a major challenge. This thesis examines the processes that courts adopt in the ascertainment and application of living customary law in Nigeria and South Africa in order to discover factors that influence the ascertainment and application of customary law. This research is qualitative in nature and utilises both doctrinal and empirical methods to make its findings. It examines the conceptualization of customary law in the context of the research against positivist and pluralist theories and analyses the doctrine of judicial discretion against relevant theories on how it impacts on the ascertainment and application process. The thesis also examines the current laws and procedures that regulate this exercise to discover how it contributes to what is ascertained by the court. For its primary sources, it utilised data obtained from the semistructured interviews conducted, and, records of proceedings of cases on customary law heard by the formal courts in Nigeria and South Africa within a fifteen-year period. The secondary and tertiary sources utilised include text books, journal articles, official reports and publications, and other literature. It identifies factors within the purview of institutional, substantive, procedural, socio-economic and political factors, as well as other factors that influence how judges exercise discretion in the ascertainment and application of living customary law. The thesis states that these factors contribute in varying degrees, to enhance or impede the ascertainment and application of living customary law by these formal courts. It therefore proposes the consideration of these factors in the policies that seek to develop measures that would enhance the ascertainment and application of living customary law by the formal courts in Nigeria and South Africa.